Arterial Spin Labeling Cerebral Perfusion Changes in Chronic Tinnitus With Tension-Type Headache - Xu, Zhen-Gui; Xu, Jin-Jing; Hu, Jinghua; Wu, Yuanqing; Wang, Dan (Frontiers in Neurology, 2021)
Background: Chronic tinnitus is accompanied with headache symptom that will influence the cerebral blood flow (CBF) and exacerbate the tinnitus severity. However, the potential relationship between tension-type headache and tinnitus remains unknown. This study will investigate whether abnormal CBF patterns exist in chronic tinnitus patients and examine the influence of headache on CBF alterations in tinnitus patients. Methods: Participants included chronic tinnitus patients (n=40) and healthy controls (n=50), well-matched for age, sex, educational and hearing level. CBF images were collected using arterial spin labeling (ASL) perfusion functional magnetic resonance imaging (fMRI). Regions with major CBF differences between tinnitus patients and healthy controls were first detected. The effects of headache on tinnitus for CBF alterations were further examined. Correlation analyses illustrated the association between CBF values and tinnitus distress as well as CBF values and headache degree. Results: Relative to healthy controls, tinnitus patients exhibited decreased CBF, mainly in right superior temporal gyrus (STG), left middle frontal gyrus (MFG), and left superior frontal gyrus (SFG); the CBF in the right STG and the left MFG was negatively associated with THQ scores (r=-0.553, p=0.001; r=-0.399, p=0.017). There was a significant effect of headache on tinnitus for CBF in the right STG. Furthermore, the headache degree was correlated positively with tinnitus distress (r=0.594, p=0.020). Conclusion: Chronic tinnitus patients exhibited reduced CBF in the auditory and prefrontal cortex. Headache may facilitate a CBF decrease in chronic tinnitus, which may underlie the neuropathological mechanisms in chronic tinnitus with headache.